An Investigation of the Effect of Meteorological Parameters on Wind Speed Estimation Using Bagging Algorithm - Emeksiz, Cem; Demir, GÃƒÂ¼lden (Prof. Dr. Ismail SARITAS, 2018)
Wind speed is the most important parameter of the wind energy conversion system. Therefore temperature, humiditiy and pressure data, which has significant effect on the wind speed, have become extremely important. In the literature, various models have been used to realize the wind speed estimation. In this study; Six different data mining algorithms were used to determine the effect of meteorological parameters on wind speed estimation. The data were collected from the measurement station established on the campus of GaziosmanpaÃ…ÂŸa University. We focused on the bagging algorithm to determine the appropriate combination of wind speed estimates.Ã‚Â The bagging algorithm was used for the first time in estimation of wind speed by taking into account meteorological parameters. To find the most efficiency method on such problem 10-fold cross validation technique was used for comparision. From results, It is concluded that bagging algorithm and temperature-humiditiy-pressure combination showed the best performance. Additionaly, temperature and pressure data are more effective in the wind speed estimation.